2023
DOI: 10.1136/bmjopen-2022-069409
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation of services along the continuum of maternal healthcare during the COVID-19 pandemic in Lubumbashi, DRC: findings from a cross-sectional household survey of women

Abstract: ObjectivesThe continuum of maternal care along antenatal (ANC), intrapartum and postnatal care (PNC) is fundamental for protecting women’s and newborns’ health. The COVID-19 pandemic interrupted the provision and use of these essential services globally. This study examines maternal healthcare utilisation along the continuum during the COVID-19 pandemic in the Democratic Republic of the Congo (DRC).DesignThis is a cross-sectional study using data collected on a survey of 599 households in Lubumbashi, DRC, usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…This was often a result of refugees’ fear of contracting COVID-19 together with poverty, which meant that they could not afford masks or the cost of private maternity services Altare et al [ 46 ] COVID-19 epidemiology and changes in health service utilization in Azraq and Zaatari refugee camps in Jordan: A retrospective cohort study Observational Secondary data analysis To describe the epidemiology of COVID-19 in Azraq and Zaatari refugee camps in Jordan and evaluate changes in routine health services during the COVID-19 pandemic Azraq and Zaatari refugee camps, Jordan Syrian war 2011 9 Refugees COVID-19 Mothers and Children ANC, FP, PNC The pandemic has both exacerbated existing inequalities and demonstrated that until all populations are included in national response plans, the world remains vulnerable to the current and the next pandemic Hossain et al [ 66 ] Exploring healthcare-seeking behavior of most vulnerable groups amid the COVID-19 pandemic in the humanitarian context in Cox’s Bazar, Bangladesh: Findings from an exploratory qualitative study Mixed-method research In-depth interviews To understand the factors influencing healthcare-seeking behavior of the most vulnerable groups during COVID-19 pandemic Ukhiya sub-district of Cox’s Bazar, Bangladesh Persecution in Myanmar 2017 3 Refugees COVID-19 Pregnant and lactating women as well as other population ANC and IPC The healthcare-seeking behavior of MVGs amid the COVID-19 pandemic in the context of Rohingya and the host communities of Cox’s Bazar was influenced by several factors ranging from socioeconomic, demographic, individual, health belief-related, and institutional factors. However, these factors are not linear rather they are intertwined, and their intersectionality represents diverse nuances of the lived realities of these most vulnerable groups during the COVID-19 pandemic Galle et al [ 49 ] Utilization of services along the continuum of maternal healthcare during the COVID-19 pandemic in Lubumbashi, DRC: findings from a cross-sectional household survey of women Cross-sectional Survey …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This was often a result of refugees’ fear of contracting COVID-19 together with poverty, which meant that they could not afford masks or the cost of private maternity services Altare et al [ 46 ] COVID-19 epidemiology and changes in health service utilization in Azraq and Zaatari refugee camps in Jordan: A retrospective cohort study Observational Secondary data analysis To describe the epidemiology of COVID-19 in Azraq and Zaatari refugee camps in Jordan and evaluate changes in routine health services during the COVID-19 pandemic Azraq and Zaatari refugee camps, Jordan Syrian war 2011 9 Refugees COVID-19 Mothers and Children ANC, FP, PNC The pandemic has both exacerbated existing inequalities and demonstrated that until all populations are included in national response plans, the world remains vulnerable to the current and the next pandemic Hossain et al [ 66 ] Exploring healthcare-seeking behavior of most vulnerable groups amid the COVID-19 pandemic in the humanitarian context in Cox’s Bazar, Bangladesh: Findings from an exploratory qualitative study Mixed-method research In-depth interviews To understand the factors influencing healthcare-seeking behavior of the most vulnerable groups during COVID-19 pandemic Ukhiya sub-district of Cox’s Bazar, Bangladesh Persecution in Myanmar 2017 3 Refugees COVID-19 Pregnant and lactating women as well as other population ANC and IPC The healthcare-seeking behavior of MVGs amid the COVID-19 pandemic in the context of Rohingya and the host communities of Cox’s Bazar was influenced by several factors ranging from socioeconomic, demographic, individual, health belief-related, and institutional factors. However, these factors are not linear rather they are intertwined, and their intersectionality represents diverse nuances of the lived realities of these most vulnerable groups during the COVID-19 pandemic Galle et al [ 49 ] Utilization of services along the continuum of maternal healthcare during the COVID-19 pandemic in Lubumbashi, DRC: findings from a cross-sectional household survey of women Cross-sectional Survey …”
Section: Resultsmentioning
confidence: 99%
“…‘Care during pregnancy and childbirth’ i.e., ANC and IPC were the domains in which most of the studies reported greater barriers [ 42 , 43 , 47 , 49 ]. The most frequently described challenges faced by women were associated with health workforce constraints for both Ebola [ 50 , 51 ], and COVID-19 [ 42 , 43 , 47 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations